R7 photoreceptor specification requires Notch activity. - Cooper, M.T.; Bray, S.J. (Current Biology, 2000)
The eight photoreceptors in each ommatidium of the Drosophila eye are assembled by a process of recruitment [1,2]. First, the R8 cell is singled out, and then subsequent photoreceptors are added in pairs (R2 and R5, R3 and R4, R1 and R6) until the final R7 cell acquires a neuronal fate. R7 development requires the Sevenless receptor tyrosine kinase which is activated by a ligand from R8 [3]. Here, we report that the specification of R7 requires a second signal that activates Notch. We found that a Notch target gene is expressed in R7 shortly after recruitment. When Notch activity was reduced, the cell was misrouted to an R1/R6 fate. Conversely, when activated Notch was present in the R1/R6 cells, it caused them to adopt R7 fates or, occasionally, cone cell fates. In this context, Notch activity appears to act co-operatively, rather than antagonistically, with the receptor tyrosine kinase/Ras pathway in R7 photoreceptor specification. We propose two models: a ratchet model in which Notch would allow cells to remain competent to respond to sequential rounds of Ras signalling, and a combinatorial model in which Notch and Ras signalling would act together to regulate genes that determine cell fate.